VD_FINDINFO HC / 2013 / 61 vom 21. Dezember 2012 - VD Tribunal cantonal (2012)
ACTION EN CONTESTATION DE L'ÉTAT DE COLLOCATION, CONTRAT D'ENTREPRISE, FORFAIT, DÉPENS | 365 al. 3 CO, 373 CO, 374 CO, 250 LP, 106 al. 1 CPC (CH), 320 CPC (CH)